A model for green supply chain management in the South African manufacturing sector - Roland Louis Epoh; Irvine Langton; Chengedzai Mafini (Cogent Business & Management, 2024)
Green supply chain management is growing as a key component of sustainability. Its implementation improves the firms' supply chain competitiveness and performance. The literature on green supply chain management in various organisations has increased over the years. However, contextual literature on green supply chain management, green capabilities and supply chain performance is still limited within the manufacturing sector in developing countries such as South Africa. The study examined the relationships between green supply chain management practices, green capabilities, and supply chain performance in the South African manufacturing sector. The study employed a quantitative method on a sample consisting of 402 supply chain professionals drawn from the manufacturing sector across the four provinces of the country (i.e. Gauteng, Free State, Limpopo, and Mpumalanga). Data were collected over six months in the second half of 2022. Hypotheses were tested using structural equation modelling based on the SMART partial least squares technique. Eco-design, green distribution, and green training impacted positively on green capabilities, the latter of which, in turn, is linked to improved agility, reliability, and reduced supply chain costs. However, green manufacturing, legislation and regulations, reverse logistics, and product returns negatively impacted green capabilities. Green capability significantly mediated the relationships between green training and distribution and eco-design, and supply chain performance. To the management and leadership in the manufacturing sector, the study suggests that the implementation of green supply chain management activities is vital in influencing green capabilities. This study contributes to green supply chain management and capabilities literature as it is one of the few studies exploring green supply chain management practices, green capabilities, and performance in the context of the South African manufacturing sector. It encourages managers to develop and implement policies to improve environmental management practices in manufacturing supply chains.
Keywords: 650; Green supply chain management; green capabilities; supply chain performance; supply chain agility; supply chain costs; supply chain reliability